Peran Perpustakaan sebagai Katalisator Berbasis Literasi Media Berkelanjutan pada Media Sosial untuk Mengatasi Digital Overstimulation - Allo, Karmila Pare; Azhari, Burnama; Nasrul, Muhammad; Syahdan, Syahdan; Ridwan, Madinatul Munawwarah (UPT Perpustakaan UIN Alauddin Makassar, 2026)
The rapid growth of digital technology has shifted the information paradigm and created new challenges. Various social media platforms such as Instagram, Twitter, TikTok, and Facebook allow users to access information continuously. This study used a qualitative approach with a content analysis method consisting of three main stages: description, reduction, and selection. Data were collected through observation, interviews, and focus group discussions (FGDs) when necessary. The results show that social media literacy is a crucial need amidst the high intensity of social media use. Lack of media literacy skills contributes to digital overstimulation among digital information users. Media literacy in this study includes the ability to identify, find, evaluate, use, and acknowledge information sources. Strengthening social media literacy is seen as a relevant strategy to respond to shifts in reading behavior and reduce the negative impacts of digital overstimulation, while strengthening the role of libraries in the digital literacy ecosystem.